Stress-corrosion-resistant high-strength mine round-link chain steel and preparation method thereof
The high-strength circular chain steel with tailored composition and microstructure effectively addresses the issue of stress corrosion in coal mining environments, enhancing durability and service life through precise thermal processing and elemental control.
Patent Information
- Application Number
- CN202411772658.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-04
AI Technical Summary
Current high-strength circular chains used in coal mining face significant challenges in maintaining durability due to corrosion in harsh underground environments, leading to premature failure and reduced service life, with a lack of focus on improving their resistance to stress corrosion cracking.
A high-strength circular chain steel composition with specific elemental percentages (C, Si, Mn, Cr, Ni, Mo, Cu, V, W) and microstructure featuring nanoscale precipitates, processed through precise thermal treatments to enhance mechanical properties and stress corrosion resistance.
The solution achieves enhanced strength, ductility, and superior stress corrosion resistance, extending the service life of the circular chains by controlling elemental composition and microstructure, while maintaining cost-effectiveness and scalability for industrial applications.
Smart Images

Figure CN119710455A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of round link chain steel, and in particular to a stress corrosion resistant high-strength round link chain steel for mining and a preparation method thereof. Background Art
[0002] Mining round link chains are transmission chains on coal mining and transportation scraper conveyors and loaders. They are both key and vulnerable parts of the equipment. Once a fracture failure occurs and the equipment stops, it will affect the entire production line and seriously affect the coal mining efficiency of the fully mechanized mining face. With the improvement of the comprehensive performance of materials used in other components of the coal mining face and the development of heavy-duty, the limitations of the round link chain material performance have restricted the improvement of equipment production capacity, and are also a prominent shortcoming that restricts the improvement of the life of the scraper conveyor.
[0003] Mining round link chains are mainly used underground, where there are a lot of corrosive media such as coal powder, rock powder, humid air, and salt dissolved in water. Oxygen is enriched and the environment is extremely complex and harsh. Although the use of round link chains places high demands on strength, toughness, fatigue performance, and wear resistance, the failure form of round link chains is largely not a simple fatigue fracture and plastic deformation fracture, but a sudden corrosion brittle fracture without deformation signs under conditions far below the yield strength. Therefore, under the premise of ensuring comprehensive mechanical properties, it is particularly necessary to pay attention to the impact of the corrosive environment on the round link chain.
[0004] Mining round-link chains are subjected to periodic tensile loads during service, with the stress distribution at the shoulder and top of the chain link being the most concentrated. For high-strength steel, local stress concentration in a corrosive environment can easily lead to stress corrosion cracking. Once stress corrosion occurs, the cracks expand rapidly in a short period of time, greatly reducing the service life of the material. Affected by underground corrosive media and wear, the surface of the round-link chain is damaged after a period of time: (1) Surface defects such as pitting and pitting are generated, and a closed cell is formed at the bottom of the pit, resulting in a decrease in the local pH value. If the conditions for the cathode hydrogen evolution reaction are met, the generated hydrogen atoms diffuse into the metal at the crack tip; (2) After plastic deformation, the fresh metal without oxide film protection is exposed to the corrosive environment again. The local electrochemical action causes the metal to dissolve as an anode, and the crack tip continues to expand. These often become the forerunners of stress corrosion cracking. For round-link chains, cracking occurs under the coupling of tensile loads and corrosive media. Therefore, improving the stress corrosion resistance of mining round-link chains can effectively extend their service life underground. However, the current focus of invention patents on high-strength round link chains for mining is mostly on improving the corrosion resistance or comprehensive wear and corrosion resistance of steel, and there is little research on the stress corrosion cracking resistance of round link chains. Therefore, how to improve the stress corrosion resistance while ensuring the high strength and toughness of mining round link chains has become an urgent problem to be solved. Summary of the invention
[0005] In view of the above situation, the present invention aims to provide a high-strength mining round link chain steel resistant to stress corrosion and a preparation method thereof, so as to solve the problem that the strength, toughness and stress corrosion resistance of existing round link chain steel cannot be effectively improved at the same time.
[0006] The purpose of the present invention is mainly achieved through the following technical solutions:
[0007] The invention provides a stress corrosion resistant high-strength mining round link chain steel. The components of the stress corrosion resistant high-strength mining round link chain steel include, by mass percentage, C: 0.22%-0.27%, Si: 0.10%-0.17%, Mn: 0.48%-0.62%, P: ≤0.015%, S: ≤0.005%, Cr: 0.41%-0.66%, Ni: 0.88%-1.23%, Mo: 0.41%-0.58%, Cu: 0.40%-0.60%, V: 0.18%-0.36%, W: 0.21%-0.45%, and the balance is Fe and unavoidable impurities.
[0008] Furthermore, the components of the stress corrosion resistant high-strength mining round link chain steel include, by mass percentage: C: 0.22% ~ 0.26%, Si: 0.10% ~ 0.16%, Mn: 0.48% ~ 0.61%, P: ≤0.015%, S: ≤0.005%, Cr: 0.41% ~ 0.61%, Ni: 0.88% ~ 1.20%, Mo: 0.41% ~ 0.55%, Cu: 0.41% ~ 0.60%, V: 0.18% ~ 0.32%, W: 0.21% ~ 0.42%, and the balance is Fe and unavoidable impurities.
[0009] Furthermore, the microstructure of the stress corrosion resistant high strength mining round link chain steel includes lath martensite and nano-scale precipitation phase.
[0010] Furthermore, in the microstructure of stress corrosion resistant high-strength mining round link chain steel, the nanoscale precipitated phase mainly includes (V, Mo, W)C composite nanoscale precipitated phase.
[0011] Furthermore, the stress intensity factor K of stress corrosion cracking of high-strength mining round link chain steel resistant to stress corrosion ISCC ≥85MPa√m.
[0012] The present invention also provides a method for preparing stress corrosion resistant high-strength mining round link chain steel, which is used to prepare the above-mentioned stress corrosion resistant high-strength mining round link chain steel, and the preparation method comprises the following steps:
[0013] Step 1, smelting and casting into billet;
[0014] Step 2, rolling the blank to obtain a bar;
[0015] Step 3: annealing and straightening the bar material and then performing heat treatment to obtain high-strength mining round link chain steel resistant to stress corrosion, wherein the heat treatment includes normalizing, quenching and tempering.
[0016] Furthermore, in step 3, the holding temperature of normalizing is 890-930°C.
[0017] Furthermore, in step 3, the quenching is performed by heating the entire furnace, heating the temperature to 860-890° C. and maintaining the temperature for 40-120 min.
[0018] Furthermore, in step 3, electromagnetic induction heating is used for quenching, the bar is heated to 900-920° C., kept warm for 3-10 seconds, and then water-cooled to room temperature.
[0019] Furthermore, in step 3, the holding temperature of tempering is 610-640°C.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] The stress corrosion resistant high-strength mining round link chain steel of the present invention is prepared by precisely controlling the contents of elements such as C, Si, Ni, Mn, Cr, Mo, Cu, and adding vanadium and tungsten to improve the strength of the steel and refine the grains; high strength, excellent toughness and plasticity, and excellent stress corrosion resistance can be obtained, and the stress corrosion resistant high-strength mining round link chain steel with excellent comprehensive performance can be obtained.
[0022] The stress corrosion resistant high-strength mining round link chain steel of the present invention has low content of expensive elements such as Mo and low cost.
[0023] In the preparation method of the stress corrosion resistant high-strength mining round link chain steel of the present invention, a normalizing + quenching + tempering process is adopted, and the parameters of each step are precisely controlled, and finally a microstructure feature containing a large number of nano-scale precipitated phases is obtained. These fine precipitated phases act as strong hydrogen traps to effectively improve the stress corrosion cracking resistance of the steel, which is very beneficial to improving the comprehensive mechanical properties of the steel.
[0024] The preparation method of the stress corrosion resistant high-strength mining round link chain steel of the present invention adopts electromagnetic induction heating to greatly shorten the heat preservation time, and cooperates with high-temperature tempering to obtain stress corrosion resistant high-strength mining round link chain steel with high strength, excellent toughness and plasticity and excellent stress corrosion resistance. The preparation method of the present invention is simple and feasible, and has the prospect of large-scale promotion and application.
[0025] The stress corrosion resistant high-strength mining round link chain steel of the present invention has high strength, good plasticity and toughness, and excellent stress corrosion resistance. Yield strength ≥1170MPa, tensile strength ≥1210MPa, cross-sectional shrinkage ≥60%, elongation after fracture ≥14%, room temperature impact toughness A kv2 ≥100J, Vickers hardness ≥390HV, stress corrosion cracking sensitivity of high-strength mining round link chain steel in Walpole corrosion inhibition solution (hydrochloric acid + sodium acetate + deionized water, pH about 3.7, room temperature) ISCC (elongation loss after fracture) ≤26.5%, ISCC (section reduction loss) ≤41.5%, stress corrosion cracking stress intensity factor K ISCC ≥85MPa√m.
[0026] Other features and advantages of the present invention will be described in the following description, and part of them will become obvious from the description, or will be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the contents particularly pointed out in the written description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings are only for the purpose of illustrating specific embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0028] Figure 1 The microstructure SEM image of Example 1;
[0029] Figure 2 This is the microstructure SEM image of Example 6;
[0030] Figure 3 TEM image of the matrix structure of Example 1;
[0031] Figure 4 TEM image of the precipitated phase of Example 1;
[0032] Figure 5 is the slow strain rate tensile curve of Example 1;
[0033] Figure 6 This is the crack growth rate curve of the wedge open loading (WOL) pre-cracked specimen in Example 1. DETAILED DESCRIPTION
[0034] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.
[0035] The invention provides a stress corrosion resistant high-strength mining round link chain steel. The components of the stress corrosion resistant high-strength mining round link chain steel include, by mass percentage, C: 0.22%-0.27%, Si: 0.10%-0.17%, Mn: 0.48%-0.62%, P: ≤0.015%, S: ≤0.005%, Cr: 0.41%-0.66%, Ni: 0.88%-1.23%, Mo: 0.41%-0.58%, Cu: 0.40%-0.60%, V: 0.18%-0.36%, W: 0.21%-0.45%, and the balance is Fe and unavoidable impurities.
[0036] The functions and dosages of the components in the present invention are described in detail below.
[0037] Carbon: Carbon is the main element for improving strength. By adding a suitable carbon content, not only can the strength of the steel be ensured, but also the hardenability of the steel can be significantly improved. However, the carbon content shall not be higher than 0.27%, otherwise the toughness and plasticity will be greatly reduced. Taking all factors into consideration, the present invention controls the carbon content to be 0.22% to 0.27%.
[0038] Silicon: One of the deoxidizing elements in steel, it is also a non-carbide forming element, with a strong solid solution strengthening effect. Silicon can effectively inhibit the precipitation of cementite, refine the size of cementite, distribute it more evenly, reduce the consumption of carbon atoms, so that the material maintains a high strength and reduces temper brittleness, but excessive Si will deteriorate the toughness and welding performance of steel. Taking the above into consideration, the silicon content of the steel of the present invention is in the range of 0.10% to 0.17%.
[0039] Manganese: Manganese has a certain solid solution strengthening effect, and can also significantly improve the hardenability of steel, with little effect on tempering stability. At the same time, it has a strong affinity with oxygen atoms, has a deoxidation effect in the smelting process, and is helpful for the subsequent desulfurization process and improves the hot processing performance of the material. However, the manganese content should not be too high, otherwise there is a tendency to coarsen the steel grains, and it may also cause segregation inside the material. The manganese content of the steel of the present invention ranges from 0.48% to 0.62%.
[0040] Chromium: It effectively improves the hardenability, corrosion resistance, oxidation resistance and wear resistance of steel, and can also effectively strengthen the matrix to improve the strength of the material. It forms a variety of carbides with carbon atoms. Its pinning effect can inhibit the grain growth at the weld joint. However, a higher Cr content is not good for welding performance. The present invention should control the Cr content within 0.41% to 0.66%.
[0041] Nickel: Nickel can improve the hardenability and corrosion resistance of steel, increase the compactness of the inner rust layer, ensure that the toughness does not decrease significantly after the strength is increased, and reduce the brittle transition temperature of steel. However, its price is high. In order to ensure that the material itself has a certain corrosion resistance, the present invention should control it within 0.88% to 1.23%.
[0042] Molybdenum: significantly improves the hardenability of steel, reduces temper brittleness, improves the impact toughness of steel, strengthens the grain boundary bonding force, and improves the delayed fracture resistance of steel. When Mo is added together with microalloying elements, it will also improve the high temperature dimensional stability of the microalloy precipitation phase, reduce its coarsening rate, and help improve the precipitation strengthening effect. However, the Mo content should not be too much, and distribution on the grain boundary will increase the brittleness of the material, and it is expensive. Therefore, the molybdenum content of the steel of the present invention is controlled at 0.41% to 0.58%.
[0043] Copper: Improves the hardenability and atmospheric corrosion resistance of steel, but Cu-containing steel is prone to hot brittleness due to selective surface oxidation. Therefore, the Cu content is controlled within 0.40% to 0.60%.
[0044] Vanadium: The VC particles precipitated from the martensite or ferrite matrix are dispersed and fine, and have a significant precipitation strengthening effect. At the same time, the formed VC particles can act as irreversible hydrogen traps to improve the hydrogen embrittlement resistance of the steel. The V content of the steel of the present invention is controlled at 0.18% to 0.36%. If it is too high, the precipitation strengthening effect will not be significantly improved, and the cost will be high.
[0045] Tungsten: Similar to molybdenum, it increases tempering stability, improves hardenability and hardness, reduces overheating sensitivity of steel, can form carbides to enhance wear resistance, and can ease the aggregation process of carbides during tempering at higher temperatures. The present invention adopts the design idea of replacing molybdenum with tungsten to reduce material costs, ensure the toughness of steel, and increase corrosion resistance and hydrogen embrittlement resistance. The tungsten content of the present invention is controlled to be 0.21% to 0.45%.
[0046] Phosphorus and sulfur: impurity elements in steel that significantly reduce plasticity, toughness and welding performance. Their contents should be controlled within 0.015% and 0.005% respectively.
[0047] Specifically, in order to further improve the comprehensive performance of the above-mentioned high-strength mining round link chain steel that is resistant to stress corrosion, the components of the above-mentioned high-strength mining round link chain steel that is resistant to stress corrosion include, by mass percentage: C: 0.22%~0.26%, Si: 0.10%~0.16%, Mn: 0.48%~0.61%, P: ≤0.015%, S: ≤0.005%, Cr: 0.41%~0.61%, Ni: 0.88%~1.20%, Mo: 0.41%~0.55%, Cu: 0.41%~0.60%, V: 0.18%~0.32%, W: 0.21%~0.42%, and the balance is Fe and unavoidable impurities.
[0048] Specifically, the microstructure of the stress corrosion resistant high-strength mining round link chain steel includes lath martensite and nano-scale precipitation phase.
[0049] Specifically, in the microstructure of the above-mentioned stress corrosion resistant high-strength mining round link chain steel, the mass percentage of the nano-scale precipitated phase is about 0.3% to 1%.
[0050] Specifically, in the microstructure of the above-mentioned high-strength mining round link chain steel with super stress corrosion resistance, the nanoscale precipitation phase mainly includes (V, Mo, W)C composite nanoscale precipitation phase.
[0051] Specifically, in the microstructure of the above-mentioned stress corrosion resistant high-strength mining round link chain steel, the average lath spacing of the lath martensite is 120 to 200 nm.
[0052] Specifically, in the microstructure of the above-mentioned stress corrosion resistant high-strength mining round link chain steel, the size of the nano-scale precipitated phase is about >0 to 25 nm.
[0053] On the other hand, the present invention also provides a method for preparing the above-mentioned stress corrosion resistant high-strength mining round link chain steel, comprising the following steps:
[0054] Step 1, smelting and casting into billet;
[0055] Step 2, rolling the blank to obtain a bar;
[0056] Step 3: annealing and straightening the bar material and then performing heat treatment to obtain high-strength mining round link chain steel resistant to stress corrosion, wherein the heat treatment includes normalizing, quenching and tempering.
[0057] Specifically, the specific steps of the above step 1 include: configuring smelting raw materials according to chemical components, raw material pretreatment, converter (or electric furnace) smelting, LF refining, RH refining, continuous casting, slag removal and slow cooling after continuous casting to obtain billets.
[0058] Specifically, in the above step 3, the holding temperature of normalizing is controlled to be 890-930° C., the holding time is 1-4 hours, and the steel is air-cooled to room temperature after being taken out of the furnace.
[0059] Specifically, in the above step 3, the quenching can be heated by a conventional heating furnace or by electromagnetic induction heating. The conventional heating furnace can be a conventional box-type high-temperature heat treatment heating furnace.
[0060] Specifically, in the above step 3, quenching is performed using a conventional heating furnace, and the specific steps include: placing the bar material into the heating furnace, heating it to 860-890° C. and keeping it warm for 40-120 minutes, and cooling it to room temperature with water after it is taken out of the furnace.
[0061] Preferably, in the above step 3, electromagnetic induction heating is used for quenching, and the specific steps include: heating the bar to 900-920° C. by electromagnetic induction heating, keeping the temperature for 3-10 seconds, and then cooling it to room temperature with water.
[0062] Specifically, in the above step 3, if the holding temperature of tempering is too high, the matrix will be severely softened and it will be difficult to maintain the strength requirements. If the holding temperature is too low, the precipitation behavior will not meet the thermodynamic requirements and the quantity will be reduced. If the holding time is too long, the precipitate phase will grow and coarsen. If the holding time is too short, the precipitate phase will not have time to precipitate. Therefore, the holding temperature of tempering is controlled to be 610-640℃, the holding time is 1.5-3.5h, and the precipitate is air-cooled to room temperature after leaving the furnace.
[0063] Specifically, the above-mentioned stress corrosion resistant high-strength mining round link chain steel has high strength, good plasticity and toughness, and excellent stress corrosion resistance. Yield strength ≥1170MPa, for example, 1173-1260MPa; tensile strength ≥1210MPa, for example, 1213-1390MPa; section shrinkage ≥60%, for example, 62%-65%; elongation after fracture ≥14%, for example, 14%-17%; room temperature impact toughness A kv2 ≥100J, for example, 102-140J; Vickers hardness ≥390HV, for example, 390-420HV. The sensitivity of stress corrosion cracking of high-strength mining round link chain steel in Walpole corrosion inhibition solution (hydrochloric acid + sodium acetate + deionized water, pH about 3.7, room temperature) is ISCC (elongation loss after fracture) ≤26.5%, for example, 23%-26.2%; ISCC (section reduction loss) ≤41.5%, for example, 40%-41.3%; stress intensity factor K of stress corrosion cracking ISCC ≥85MPa√m, for example, 87~93MPa√m.
[0064] The stress corrosion resistant high-strength mining round link chain steel of the present invention is prepared by precisely controlling the contents of elements such as C, Si, Ni, Mn, Cr, Mo, Cu, and adding vanadium and tungsten to improve the strength of the steel and refine the grains; high strength, excellent toughness and plasticity, and excellent stress corrosion resistance can be obtained, and the stress corrosion resistant high-strength mining round link chain steel with excellent comprehensive performance can be obtained.
[0065] The stress corrosion resistant high-strength mining round link chain steel of the present invention has low content of expensive elements such as Mo and low cost.
[0066] In the preparation method of the stress corrosion resistant high-strength mining round link chain steel of the present invention, a normalizing + quenching + tempering process is adopted, and the parameters of each step are precisely controlled, and finally a microstructure feature containing a large number of nano-scale precipitated phases is obtained. These fine precipitated phases act as strong hydrogen traps to effectively improve the stress corrosion cracking resistance of the steel, which is very beneficial to improving the comprehensive mechanical properties of the steel.
[0067] The preparation method of the stress corrosion resistant high-strength mining round link chain steel of the present invention adopts electromagnetic induction heating to greatly shorten the heat preservation time, and cooperates with high-temperature tempering to obtain stress corrosion resistant high-strength mining round link chain steel with high strength, excellent toughness and plasticity and excellent stress corrosion resistance. The preparation method of the present invention is simple and feasible, and has the prospect of large-scale promotion and application.
[0068] The stress corrosion resistant high-strength mining round link chain steel of the present invention has high strength, good plasticity and toughness, and excellent stress corrosion resistance. Yield strength ≥1170MPa, tensile strength ≥1210MPa, cross-sectional shrinkage ≥60%, elongation after fracture ≥14%, room temperature impact toughness A kv2 ≥100J, Vickers hardness ≥390HV, stress corrosion cracking sensitivity of high-strength mining round link chain steel in Walpole corrosion inhibition solution (hydrochloric acid + sodium acetate + deionized water, pH about 3.7, room temperature) ISCC (elongation loss after fracture) ≤26.5%, ISCC (section reduction loss) ≤41.5%, stress corrosion cracking stress intensity factor K ISCC ≥85MPa√m.
[0069] The advantages of precise control of the composition and process parameters of the steel of the present invention are demonstrated below with specific examples and comparative examples.
[0070] Examples 1-7 (A1-A7 in the table) of the present invention provide a high-strength round-link chain steel for mining that is resistant to stress corrosion and a preparation method thereof. The chemical compositions of the steels of Examples 1-7 are shown in Table 1.
[0071] The method for preparing the steel of Examples 1-5 comprises:
[0072] The smelting raw materials are configured according to the above chemical components, and are subjected to pretreatment, converter smelting, LF refining, RH refining, and slab continuous casting, followed by slag removal and slow cooling. The continuous casting slab is heated in a heating furnace and then rolled into a round bar with a diameter of 48 mm, and then annealed and straightened.
[0073] The round bar wire is cut into appropriate lengths and the whole section is placed in a heating furnace for heat treatment: normalizing temperature 890-930°C, keep warm for 1-4 hours and then air cool; quenching temperature 860-890°C, keep warm for 40-120 minutes and then water cool; tempering temperature 610-640°C, keep warm for 1.5-3 hours and then air cool.
[0074] The method for preparing the steel of Examples 6-7 comprises:
[0075] The smelting raw materials are configured according to the above chemical components, and are subjected to pretreatment, converter smelting, LF refining, RH refining, and slab continuous casting, followed by slag removal and slow cooling. The continuous casting slab is heated in a heating furnace and then rolled into a round bar with a diameter of 48 mm, and then annealed and straightened.
[0076] The round bar wire is cut into appropriate lengths, and the whole section is placed in a heating furnace for normalizing treatment: the normalizing temperature is 890-930°C, and it is kept warm for 1-4 hours and then air-cooled; the electromagnetic induction heating quenching temperature is 900-920°C, and it is kept warm for 5 seconds and then immediately cooled; the whole section is placed in a heating furnace for tempering treatment: the tempering temperature is 610-640°C, and it is kept warm for 1.5-3 hours and then air-cooled.
[0077] The specific process parameters of the heat treatment of Examples 1-7 are shown in Table 2; the microstructure of the stress corrosion resistant high-strength mining round link chain steel is shown in Table 3, and the mechanical properties test results of the stress corrosion resistant high-strength mining round link chain steel are shown in Table 4.
[0078] Figure 1 The microstructure SEM image of Example 1; Figure 2 This is the microstructure SEM image of Example 6; Figure 3 TEM image of the matrix structure of Example 1; Figure 4 TEM image of the precipitated phase of Example 1; Figure 5 is the slow strain rate tensile curve of Example 1; Figure 6 This is the crack growth rate curve of the wedge open loading (WOL) pre-cracked specimen in Example 1.
[0079] The inventor has conducted a large number of experimental studies during the research process, and now uses some solutions with poor performance as comparative examples.
[0080] Comparative Example 1
[0081] This comparative example provides a steel for a mining round link chain and a preparation method thereof. The components thereof are shown in Table 1, and the specific process parameters of the preparation method are shown in Table 2.
[0082] The ingredients of this comparative example are not within the scope of this application, and some process parameters of the preparation method do not meet the requirements. Therefore, the grain size in the microstructure of this comparative example is relatively large and the stress corrosion resistance is relatively poor.
[0083] Comparative Example 2
[0084] This comparative example provides a steel for a mining round link chain and a preparation method thereof. The components thereof are shown in Table 1, and the specific process parameters of the preparation method are shown in Table 2.
[0085] The composition of this comparative example is not within the scope of the present application, the amount of nano-precipitated phase in the microstructure of this comparative example is small, and the stress corrosion resistance is poor.
[0086] Comparative Example 3
[0087] This comparative example provides a steel for a mining round link chain and a preparation method thereof. The components thereof are shown in Table 1, and the specific process parameters of the preparation method are shown in Table 2.
[0088] The composition of this comparative example is not within the scope of the present application. The size of the precipitated phase in the microstructure of this comparative example is relatively large, and the stress corrosion resistance is relatively poor.
[0089] The round link chain steels of the embodiments of the present invention and comparative examples (B1-B3) were prepared into samples meeting the requirements of national standards after heat treatment for inspection and testing.
[0090] The steel for round link chain of the embodiment of the present invention and the comparative example was subjected to slow strain rate tensile test and wedge open loading (WOL) pre-crack specimen stress corrosion test according to GB / T15970 and GB / T12445 standards, and the test samples were prepared according to the standard requirements. Among them, the slow strain rate tensile test environment: in air and Walpole corrosion inhibition solution (hydrochloric acid + sodium acetate + deionized water, pH about 3.7, room temperature), the stretching rate was 1×10 -6 s -1 The surface of the sample is smooth. The changes in the length dimension and the diameter of the necking section before and after the sample is broken are measured respectively, and the elongation after fracture A and the section shrinkage Z are calculated. After the test is completed, the stress corrosion sensitivity index is calculated according to the formula ISCC = (Ia-Is) / Ia, where Ia is the experimental parameter in air; Is is the experimental parameter in Walpole corrosion inhibitor. The stress corrosion test environment of the wedge-shaped open loading (WOL) pre-cracked sample: Walpole corrosion inhibitor (hydrochloric acid + sodium acetate + deionized water, pH is about 3.7, temperature 35±0.5℃), the value of the stress intensity factor is calculated by measuring the crack length and other related parameters, and the specific calculation method refers to the content of GB / T12445 standard.
[0091] Table 1 Chemical composition, wt%
[0092]
[0093]
[0094] Table 2 Specific process parameters
[0095]
[0096] Table 3 Microstructure of steel
[0097]
[0098]
[0099] Table 4 Mechanical properties of steel
[0100]
[0101] Table 5 Results of slow strain rate tensile test and stress corrosion test of wedge open loading (WOL) pre-cracked specimens
[0102]
[0103]
[0104] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A stress corrosion resistant high-strength round link chain steel for mining, characterized in that: The components of the stress corrosion resistant high-strength mining round link chain steel include, by mass percentage, C: 0.22% to 0.27%, Si: 0.10% to 0.17%, Mn: 0.48% to 0.62%, P: ≤0.015%, S: ≤0.005%, Cr: 0.41% to 0.66%, Ni: 0.88% to 1.23%, Mo: 0.41% to 0.58%, Cu: 0.40% to 0.60%, V: 0.18% to 0.36%, W: 0.21% to 0.45%, and the balance is Fe and unavoidable impurities.
2. The stress corrosion resistant high-strength round link chain steel for mining use according to claim 1, characterized in that: The components of the stress corrosion resistant high-strength mining round link chain steel include, by mass percentage, C: 0.22% to 0.26%, Si: 0.10% to 0.16%, Mn: 0.48% to 0.61%, P: ≤0.015%, S: ≤0.005%, Cr: 0.41% to 0.61%, Ni: 0.88% to 1.20%, Mo: 0.41% to 0.55%, Cu: 0.41% to 0.60%, V: 0.18% to 0.32%, W: 0.21% to 0.42%, and the balance is Fe and unavoidable impurities.
3. The stress corrosion resistant high-strength round link chain steel for mining use according to claim 1, characterized in that: The microstructure of the stress corrosion resistant high-strength mining round link chain steel includes lath martensite and nano-scale precipitation phase.
4. The stress corrosion resistant high-strength round link chain steel for mining use according to claim 3, characterized in that: In the microstructure of the stress corrosion resistant high-strength mining round link chain steel, the nanoscale precipitation phase mainly includes a (V, Mo, W)C composite nanoscale precipitation phase.
5. The stress corrosion resistant high-strength round link chain steel for mining use according to claim 1, characterized in that: The stress intensity factor K of the stress corrosion cracking of the high-strength mining round link chain steel resistant to stress corrosion ISCC ≥85MPa√m.
6. A method for preparing stress corrosion resistant high-strength round-link chain steel for mining, characterized in that: The preparation method is used to prepare the stress corrosion resistant high-strength mining round link chain steel according to any one of claims 1 to 5, and the preparation method comprises the following steps: Step 1, smelting and casting into billet; Step 2, rolling the blank to obtain a bar; Step 3: annealing and straightening the bar material and then performing heat treatment to obtain high-strength mining round link chain steel resistant to stress corrosion, wherein the heat treatment includes normalizing, quenching and tempering.
7. The preparation method according to claim 6, characterized in that: In step 3, the holding temperature of normalizing is 890-930°C.
8. The preparation method according to claim 6, characterized in that: In the step 3, the quenching is carried out by heating the heating furnace as a whole, heating the temperature to 860-890° C. and keeping the temperature for 40-120 minutes.
9. The preparation method according to claim 6, characterized in that: In the step 3, electromagnetic induction heating is used for quenching, the bar is heated to 900-920° C., kept warm for 3-10 seconds, and then water-cooled to room temperature.
10. The preparation method according to any one of claims 6 to 9, characterized in that: In the step 3, the holding temperature of the tempering is 610-640°C.
Citation Information
Patent Citations
Steel for heat-resisting casing pipe and manufacturing method thereof
CN101748330A
Oceanic mooring chain steel with low environmental crack sensitivity and ultrahigh obdurability and preparation method thereof
CN103667953A
130KSI-grade and 135KSI-grade corrosion-resistant drill tool steel for oil and gas fields and manufacturing method thereof
CN107177797A
Corrosion-resistant mining high-strength round-link chain steel and manufacturing method thereof
CN116463551A
Scraper chain steel, preparation method of scraper chain steel, scraper chain and preparation method of scraper chain
CN116837290A
Cited By
Steel for high-strength mining round-link chain and manufacturing method thereof
CN120776207A